Pemberdayaan Masyarakat dalam Mengatasi Kenakalan Remaja di Desa Kukutio Kecamatan Watubangga Kabupaten Kolaka - Juliatmaja, Aan Wilhan; Hasyim, Rifki; Maulyanti, Restina; Alfionita, Reka; Nurcahyani, Nurcahyani; Jumria, Jumria; Selfi, Selfi; Mirna, Mirna; Aulia S, Diva Adhiesti; Salsabila, Ilmi; Yasmin, Yasmin; As’ad, Muhammad; Ibrahim, Ibrahim (Universitas Pahlawan Tuanku Tambusai, 2025)
Juvenile delinquency is an increasingly worrying social problem in various regions. This phenomenon not only impacts the adolescent individual himself, but also affects the family, the surrounding environment, and society in general. Lack of attention, lack of positive activities, weak social control, and lack of community participation are the main triggers for the increase in juvenile delinquency. Thus, community empowerment efforts are needed aimed at preventing and overcoming juvenile delinquency through a participatory and community-based approach. Training and counselling methods are carried out to the community, parents, and adolescents about the dangers of juvenile delinquency and how to prevent it. The results of this activity are increasing public and parental awareness of the importance of their role in fostering adolescents, the formation of forums or communities of positive adolescents who are active in the community, the decrease in the number of juvenile delinquency in the area of implementation of the activity, documentation and modules of empowerment activities that can be replicated in other areas, and the building of networks between the community, the government, and educational institutions in dealing with juvenile delinquency in a systematic manner Sustainable.